An Overview of the Knowledge and Awareness of Type II Diabetes Mellitus Patients about the Disease, Related Risk Factors, and Complications: A Literature Review - Ali A. Alyahawi; Mohammed AW. Almorish (Disease and Health Research: New Insights Vol. 5, 2024)
Background: Diabetes mellitus (DM) is a major public health concern, leading to increased morbidity, mortality, healthcare utilization, and costs. The prevalence of diabetes has increased significantly, so knowledge and awareness are crucial for diabetes management, and self-management education is essential for successful treatment. However, knowledge of diabetes is often poor in developing countries. Illiteracy rates are higher in these countries compared to the developed countries, which contributes to lower knowledge and awareness of diabetes among diabetic patients. Objectives: The objective of this study is to summarize peer-reviewed publications for a selected period (13 years) about patients’ knowledge and awareness of diabetes mellitus type 2. Methodology: A total of 13 articles were selected as cross-sectional studies or systemic reviews from literature review using three databases, namely Google Sholar, PubMed, and ResearchGate, and were published in 2011-2023. Results: Most previous cross-sectional studies reported that educational interventions led to significant increases in participants’ knowledge of type 2 diabetes and high educational qualifications were significantly related to a better understanding of diabetes. In a multivariate analysis, greater diabetes awareness, greater medication adherence and monotherapy use were significant factors in good glycemic control. Other previous cross-sectional studies and systemic reviews indicated that most people with diabetes understand that lifestyle changes are necessary to treat diabetes. However, many also believe that diabetes can be permanently cured and that being overly healthy can lead to diabetes. Also, Lower frequency of HbA1c monitoring is significantly associated with poor glycemic control. Moreover, the results showed that people with diabetes may have poorer control if they have had diabetes for a longer duration. Conclusion: The source of information obtained is used as a reference for knowledge and behavior formation. Providing education can be applied to increase patient knowledge about diabetic mellitus, risk factors, and complications.